Ginsenoside Rh2 repressed the progression of prostate cancer through the mitochondrial damage induced by mitophagy and ferroptosis - He, Zhen; Shi, Jianxi; Zhu, Bing; Tian, Zhentao; Zhang, Zhihong; Zhang, Changwen (Frontiers in Oncology, 2025)
IntroductionProstate cancer (PC), the most common male genitourinary malignancy and second leading cause of global cancer deaths in men, frequently progresses to lethal castration-resistant PC (CRPC). Ginsenoside Rh2 (GRh2), a ginseng-derived bioactive compound, exhibits antitumor potential, but its efficacy and mechanisms in PC remain unclear.MethodsPC3 cells were treated with GRh2 to assess proliferation (IC50 calculation), migration, and invasion. Mitochondrial function (membrane potential, ROS, ATP/ADP), mitophagy markers (PINK1/Parkin, VDAC1/TOM20, autophagosomes), and ferroptosis indicators (lipid ROS, MDA, Fe2+, GSH, SLC7A11/GPX4) were evaluated. Specific inhibitors (Mdivi-1 for mitophagy, Fer-1 for ferroptosis) validated mechanistic causality. Subcutaneous xenograft models in nude mice assessed in vivo efficacy.ResultsGRh2 potently inhibited PC3 cell proliferation (IC50 = 19.3 μg/mL), migration, and invasion. It induced mitochondrial dysfunction (depolarized membrane, elevated ROS, disrupted ATP/ADP) and activated mitophagy, evidenced by upregulated PINK1/Parkin, reduced VDAC1/TOM20, and autophagosome accumulation. Concurrently, GRh2 triggered ferroptosis via lipid ROS accumulation, increased MDA/Fe2+, GSH depletion, and SLC7A11/GPX4 downregulation. All effects were reversed by Mdivi-1 or Fer-1, confirming pathway-specific causality. In vivo, GRh2 significantly suppressed tumor growth.DiscussionThis study provides the first evidence that GRh2 exerts synergistic antitumor effects in PC through dual induction of mitophagy-associated mitochondrial damage and ferroptosis. The reversibility of both pathways by specific inhibitors establishes a causal mechanistic framework. GRh2 thus represents a multifaceted therapeutic agent against PC by targeting mitochondrial integrity.